NMR metabolic profiling of the liver following administrationof alcohol andthemushroom Ganoderma lucidum in rats - M. S. Krestina; O. B. Shevelev; I. V. Koptyug; L. A. Gerlinskaya; S. E. Peltek; A. E. Akulov (Вавиловский журнал генетики и селекции)
We have evaluated the efficiency of a metabonomic approach to metabolic phenotyping and detection of early metabolic changes under a toxic influence. For this purpose, a metabolic profiling of rat liver was performed with 1H NMR spectroscopy. Rat tissues from animals in three groups were analyzed. Group C consisted of control animals; animals in group A received alcohol repeatedly (15 % ethanol); and animals in group A+ R received alcohol in combination with a hepatoprotective herbal medicine (Reishi, Ganoderma lucidum) repeatedly. Noteworthy, alcohol consumption did not cause pathological changes, but stimulated hepatocyte proliferation. Our data suggest that changes in metabolite concentrations in A represent a typical metabolic response to alcohol consumption, namely decrease in glycine, leucine, isoleucine, valine, choline and lactate content, and increase in TMAO content. Treatment with Reishi (A+ R) had positive effects, in that it restored the levels of glycine, valine and TMAO. Furthermore, increase in NAD, ATP, UTP, succinate, pyranose, and acetate concentrations was observed in A+ R. A correlation was found between the valine, isoleucine, lactate, choline, and pyranose content and the number of binuclear hepatocytes. Binuclear hepatocytes indicate proliferative activity, and the concentration of the metabolites participating in the formation of new hepatic cells decreases. Thus, the study of liver tissues by 1H NMR spectroscopy allows for detection of early changes in metabolite concentrations following chronic consumption of alcohol at insignificant doses. Consequently, 1H NMR spectroscopy can serve as a promising approach to detecting alcohol-related liver pathologies and assessing the efficiency of the therapy used.